In vivo Estimation of Breast Cancer Tissue Volume in Subcutaneous Xenotransplantation Mouse Models by Using a High-Sensitivity Fiber-Based Terahertz Scanning Imaging System - Chen, Hua; Han, Juan; Wang, Dan; Zhang, Yu; Li, Xiao; Chen, Xiaofeng (Frontiers in Genetics, 2021)
Absorption contrast between the terahertz (THz) frequency range of fatty and cancer tissues allows cancer diagnosis by THz imaging. We successfully demonstrated the ability of THz imaging to measure small breast cancer volume in the subcutaneous xenotransplantation mouse models even without external comparison. We estimated the volume detection limitation of the fiber-based THz scanning imaging system using a highly sensitive cryogenic-temperature operated Schottky diode detector to be smaller than 1 mm3, thus showing the potential application of this technique in preliminary early cancer diagnosis.